Estudo do processo combinado de extração em altas pressões e purificação do óleo de candeia pelo processo de adsorção em coluna de leito fixo - Ribas, Marielen Cozer (2012)
The Candeia (Eremanthus erythropappus) has a rich oil in α-bisabolol, a substance of high commercial value and wide industrial application. An alternative to traditional methods of extraction and / or fractionation of the candeia oil is the use of supercritical technology, with the advantage of not having the disadvantages of thermal degradation and the use of organic solvents. Thus, this research aims to evaluate the combined process of supercritical extraction and purification of the candeia oil by adsorption in fixed bed column. For the extractor packaging were used 42g of candeia wood with a particle size from 28 to 32 mesh. For the extraction were evaluated two solvents, supercritical carbon dioxide and propane pressurized. The experiments were conducted at temperatures of 40, 50 and 60 °C and pressures of 100, 120, 150, 200 and 245 bar for carbon dioxide. For propane, the temperature conditions studied were 30, 55 and 80 °C and pressures of 80, 100 and 120 bar; for the experiments with propane was performed a 22 factorial design with the focal point in triplicate. The effect of the temperature and pressure in the ratio of oil mass extracted per mass of solvent was evaluated for the different experimental conditions. For carbon dioxide the condition with the highest yield was at 60 ° C and 245 bar, while for propane, the best condition was 60 ° C and 80 bar. As the ratio of oil mass / solvent mass, the best operating conditions are 40 º C and 200 bar for CO 2 and 80 ° C and 80 bar for propane. From the experimental data of the kinetics of extraction, the mathematical model of Sovová was tested, which satisfactorily represented the experimental data. The results showed that extraction with pressurized propane presented higher extraction rate and content of α-bisabolol when compared to carbon dioxide, dichloromethane and hexane, indicating that propane is the most appropriate solvent for the extraction of oil from the candeia wood. To obtain a rich oil in -bisabolol a purification was performed under income yield higher conditions. Of the tested adsorbents, the silica gel presented greater capacity for purification of the extract than alumina.